Development of performance, physiological and technical capacities during a six-month cross-country skiing talent transfer program in endurance athletes - Talsnes, R. K.; Hetland, T.-A.; Cai, X.; Sandbakk, Ø. (Frontiers in Sports and Active Living, 2020)
Purpose: To examine the development of performance, physiological and technical capacities as well as the effect of sport background among runners, kayakers and rowers when transferred to cross-country (XC) skiing over a 6-month training period.